Sistem Pengendalian Intern pada Perusahaan Kecil dan Menengah - Kurniawati, Heny (Bina Nusantara University, 2011)
The effective Internal Control System plays fundamental role in a strong corporate governance. This case study describes and discusses how theÂ implementasionÂ of internal control system in small and medium companies, the characteristics, and the weaknesses and strengths of internal control in the companies. This case study shows that the characteristics of small and medium companies contribute to the weaknesses and strengths of internal control they have. The understanding of the characteristics and effectiveness of small and medium companies internal control will help auditors to conduct financial audit as well as performance audit.